2013
DOI: 10.1590/s0103-84782013000900015
|View full text |Cite
|
Sign up to set email alerts
|

Inquérito sorológico e molecular da brucelose canina no município de Natal, Estado do Rio Grande do Norte

Abstract: O objetivo do presente trabalho foi determinar a ocorrência de anticorpos anti-Brucella rugosa e anti-Brucella lisa em cães do município de Natal, Estado do Rio Grande do Norte, Brasil, bem como identificar fatores de risco associados à positividade e realizar a detecção molecular em animais soropositivos. Foram utilizados soros sanguíneos de 416 cães atendidos em clínicas veterinárias durante o período de março a novembro de 2011. Para o diagnóstico sorológico da infecção por Brucella rugosa, foi empregada a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…78 In Brazil, B. canis infection in dogs has been demonstrated mainly by serologic surveys, with frequencies of seropositive dogs of 0-54.8%. 1,3,16,17,[23][24][25][26][27]73,77,80 Such studies used a single test method, and AGID with B. ovis antigen was the most widely employed, with or without serum treatment with 2-ME. AGID is a low-cost assay, it is simple to perform, and it has analytical sensitivity levels similar to CFT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 In Brazil, B. canis infection in dogs has been demonstrated mainly by serologic surveys, with frequencies of seropositive dogs of 0-54.8%. 1,3,16,17,[23][24][25][26][27]73,77,80 Such studies used a single test method, and AGID with B. ovis antigen was the most widely employed, with or without serum treatment with 2-ME. AGID is a low-cost assay, it is simple to perform, and it has analytical sensitivity levels similar to CFT.…”
Section: Discussionmentioning
confidence: 99%
“…84 Previous studies, mostly based on serology, have demonstrated the presence of B. canis in various Brazilian regions, affecting dogs in commercial kennels, households, or street dogs in urban or rural areas. 3,16,17,23,24,26,27,50,65,73,77,80 However, marked variations in B. canis infection frequency or prevalence among different surveys have been observed, possibly as a result of the use of different tests. Our goal was to compare different serologic methods and PCR used in the detection of B. canis infection in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…A infecção é considerada endêmica no Brasil, tendo sido relatada em diversos estados com frequências de ocorrência variáveis conforme as populações caninas examinadas e os métodos de diagnóstico utilizados (Silva et al, 2012;Dreer et al, 2013;Fernandes et al, 2013;Machado et al, 2013;Santana et al, 2013;Paz et al, 2015;Mascolli et al, 2016;. Não há vacina disponível para a prevenção da brucelose nos cães e a infecção é de difícil tratamento.…”
Section: Mvandzunclassified
“…De acordo com López et al (2009) não há como estimar a prevalência global da brucelose em cães e pouco esforço tem sido feito para o controle da doença, exceto algumas iniciativas particulares direcionadas a determinadas raças de cães e em canis comerciais. No Brasil, a ocorrência da brucelose canina foi mensurada através de estudos soroepidemiológicos, microbiológicos e moleculares em diversas localidades do país e de acordo com os dados obtidos a frequência da B. canis variou de 0,3% a 54,77%, conforme verificado no quadro 1 (CARVALHO et al, 2000;AZEVEDO et al, 2003;ALMEIDA et al, 2004;KEID et al, 2004;AGUIAR et al, 2005;CAVALCANTI et al, 2006;FERREIRA, et al, 2007;MALEK dos REIS et al, 2008;VASCONCELOS et al, 2008;DORNELES et al, 2011;FERNANDES et al, 2011;SILVA et al, 2012;DREER et al, 2013;FERNANDES et al, 2013;MACHADO et al, 2013;SANTANA et al, 2013;PAZ et al, 2015;MASCOLLI et al, 2016). SANFORD, 1975;MUNDFORD et al, 1975;ROXO et al, 1990;AZEVEDO et al, 2003;LUCERO et al, 2005b;CORBEL et al, 2006;DENTINGER et al, 2012;KRUEGER et al, 2014 POLT et al, 1982;TOSI;NELSON, 1982;RUMLEY;CHAPMAN, 1986;ROXO et al, 1990;YING;NGUYEN;JAHRE, 1999;PIAMPIANO et al, 2000;…”
Section: Revisão De Literaturaunclassified